2018
DOI: 10.1042/bcj20170601
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on the transglutaminase 2 gene: a focus on genomic and transcriptional aspects

Abstract: The type 2 isoenzyme is the most widely expressed transglutaminase in mammals displaying several intra- and extracellular activities depending on its location (protein modification, modulation of gene expression, membrane signalling and stabilization of cellular interactions with the extracellular matrix) in relation to cell death, survival and differentiation. In contrast with the appreciable knowledge about the regulation of the enzymatic activities, much less is known concerning its inducible expression, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 114 publications
0
22
0
Order By: Relevance
“…Transglutaminase 2 (TG2) is a 78-kDa calcium-dependent enzyme of the protein-glutamine γ-glutamyl-transferase family 5 , 6 . In the presence of calcium, TG2 functions as a catalytic enzyme that modifies the protein-bound glutamine side chains, resulting in protein crosslinking through transamidation or deamidation 6 , 7 . When this protein binds to GTP intracellularly, it becomes closed conformationally and acts as a G-protein associated signaling molecule 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Transglutaminase 2 (TG2) is a 78-kDa calcium-dependent enzyme of the protein-glutamine γ-glutamyl-transferase family 5 , 6 . In the presence of calcium, TG2 functions as a catalytic enzyme that modifies the protein-bound glutamine side chains, resulting in protein crosslinking through transamidation or deamidation 6 , 7 . When this protein binds to GTP intracellularly, it becomes closed conformationally and acts as a G-protein associated signaling molecule 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the present study showed no significant association between exon 6 (E469K) of ICAM-1 polymorphism and DS. The inclusion and exclusion criteria of the patients with DS and the prescribed medicines were different between the present study and the study by Dore et al Type-2 transglutaminase (TGM2/TG2) is emerging as a multifunctional enzyme that is capable of promoting specialized enzyme functions under regulation by allosteric effectors depending on its cellular location such as angiogenesis, cell growth/differentiation, and cell death [17,18]. TGM2 acts as a G protein in signal transduction processes and is involved in the pathophysiology of various inflammatory conditions.…”
Section: Discussionmentioning
confidence: 63%
“…TGM2 acts as a G protein in signal transduction processes and is involved in the pathophysiology of various inflammatory conditions. TGM2 is associated with 329 diseases, including immune system, endocrine, metabolic, cardiovascular, epidermal, renal and hematological diseases [17]. Bradford et al genotyped eight SNPs (rs2076380, rs7270785, rs4811528, rs2284879, rs6023526, rs2268909, rs17789815 and rs1555074) related to the TGM2 gene in individuals with schizophrenia in a British population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of TG2 is tightly controlled and can be induced at the transcriptional level by cytokines and the activation of various transcription factors [40,41]. Moreover, the alternative splicing of TG2 gene ( TGM2 ) mRNA has been observed [42,43].…”
Section: Tissue Transglutaminase Descriptionmentioning
confidence: 99%